PENGARUH COUNTRY OF ORIGIN DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN DENGAN PERSEPSI SEBAGAI FAKTOR MEDIASI PADA PRODUK COSRX - Aprilia, I Gusti Ayu Sinta Dewi; Putri Prawitasari , Putu; Ayu Tirtayani, I Gusti; Anjani, Ni Ketut (LP2M Universitas Bina Bangsa, 2025)
One of the popular skincare brands is COSRX which has gained popularity in various countries including Indonesia because of its innovative formulation and recognized quality. This study aims to determine the influence of Country of Origin and product quality on consumer buying interest with perception as a mediating factor in COSRX products. This study uses the purposive sampling method in taking samples with a total of 100 respondents. The data collection method is carried out by distributing questionnaires directly at cosmetic stores or through Google Forms distributed on social media such as WhatsApp and Instagram. Data analysis uses multiple linear regression analysis with SPSS 25 for windows program. Based on statistical methods, validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, normality tests, multiple linear regression tests, partial tests, simultaneous tests and determination coefficient tests were carried out. The results of the study show that product quality and consumer perception play a major role in influencing purchasing decisions.